Modernist Legacies
IX, 263 p.
Keywords: The first collection of essays dedicated to experimental practice in contemporary British poetry, Modernist Legacies provides an overview of the most notable trends in the past 50 years. Contributors discuss a wide range of poets including Caroline Bergvall and Barry MacSweeney, showing these poets' connections with their Modernist predecessors.